2019
DOI: 10.2196/14108
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Machine Learning Algorithms for the Diagnosis of Autism Spectrum Disorder: Systematic Review and Meta-Analysis of Brain Magnetic Resonance Imaging Studies

Abstract: Background In the recent years, machine learning algorithms have been more widely and increasingly applied in biomedical fields. In particular, their application has been drawing more attention in the field of psychiatry, for instance, as diagnostic tests/tools for autism spectrum disorder (ASD). However, given their complexity and potential clinical implications, there is an ongoing need for further research on their accuracy. Objective This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…Further, we currently do not have a su cient understanding of "what would work for whom", thereby limiting opportunities for maximizing outcomes for children and their families with economic rami cations for broader society. In this context, ML algorithms have been found to be useful in predicting diagnostic accuracy in ASD with neuroimaging data [58]. Further, one recent study used Gaussian Mixture Models and Hierarchical Agglomerative Clustering, which provide a statistical framework for learning latent cluster memberships to determine ASD subgroups with differentiated treatment responses [59].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we currently do not have a su cient understanding of "what would work for whom", thereby limiting opportunities for maximizing outcomes for children and their families with economic rami cations for broader society. In this context, ML algorithms have been found to be useful in predicting diagnostic accuracy in ASD with neuroimaging data [58]. Further, one recent study used Gaussian Mixture Models and Hierarchical Agglomerative Clustering, which provide a statistical framework for learning latent cluster memberships to determine ASD subgroups with differentiated treatment responses [59].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 study by Moon et al [22], 40 machine learning algorithm studies for ASD published between 2007 and 2018 were systematically reviewed and meta-analysis was conducted. Among them, meta-analysis of 12 samples using structural MRI revealed that the integrated sensitivity was 0.83, specificity was 0.84, and area under the curve/partial area under the curve (AUC/pAUC) was 0.90/0.83.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…fMRI measures neural activity using blood oxygenationlevel dependent (BOLD) differences. A 2019 meta-analysis study conducted on fMRI and machine learning algorithm studies on ASD published between 2007 and 2018 [22] found the integrated sensitivity to be 0.69, specificity to be 0.66, and AUC/pAUC to be 0.71.…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%
“…Dieser MRT-basierte Ansatz erlaubte es dann, die Einteilung zwischen diesen beiden Störungen in einer separaten Patientenpopulation mit einer nahezu 70%igen Genauigkeit zu trennen [32]. Darüber hinaus finden ähnliche gelagerte Ansätze auch Anwendung im Bereich Autismus [33,34], Substanzabhängigkeiten [35] und Persönlichkeitsstörungen [36][37][38]. Diese Studien liefern somit klare Hinweise dafür, dass die in diagnostischen Studien erlernten neuroanatomischen Signaturen als klinische Entscheidungshilfen verwendet werden können.…”
Section: Diagnostikunclassified